2021
DOI: 10.3390/biom11030479
|View full text |Cite
|
Sign up to set email alerts
|

Insight into Inhibitory Mechanism of PDE4D by Dietary Polyphenols Using Molecular Dynamics Simulations and Free Energy Calculations

Abstract: Phosphodiesterase 4 (PDE4), mainly present in immune, epithelial, and brain cells, represents a family of key enzymes for the degradation of cyclic adenosine monophosphate (cAMP), which modulates inflammatory response. In recent years, the inhibition of PDE4 has been proven to be an effective therapeutic strategy for the treatment of neurological disorders. PDE4D constitutes a high-interest therapeutic target primarily for the treatment of Alzheimer’s disease, as it is highly involved in neuroinflammation, lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 80 publications
0
22
0
Order By: Relevance
“…The inverse molecular docking protocol based on the CANDOCK algorithm resulted in score variations for the detection of true target proteins (TG determined from PC has a value of 0.171), which in combination with ROC AUC above 0.6 indicates that the protocol provides good results in agreement with the experiments [ 61 ]. Moreover, our inverse molecular docking protocol has been already extensively validated by Fine and Konc et al [ 55 ], Furlan et al [ 50 , 130 ], Kores et al [ 49 , 131 ], and Jukič et al [ 132 ] using different molecules of interest.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inverse molecular docking protocol based on the CANDOCK algorithm resulted in score variations for the detection of true target proteins (TG determined from PC has a value of 0.171), which in combination with ROC AUC above 0.6 indicates that the protocol provides good results in agreement with the experiments [ 61 ]. Moreover, our inverse molecular docking protocol has been already extensively validated by Fine and Konc et al [ 55 ], Furlan et al [ 50 , 130 ], Kores et al [ 49 , 131 ], and Jukič et al [ 132 ] using different molecules of interest.…”
Section: Resultsmentioning
confidence: 99%
“…Natural plant-based compounds play an important role in the development of novel drugs as they may possess several advantages over conventional synthetic compounds, namely, fewer side effects, lower long-term toxicity, and versatile biological effects [ 130 ]. We report the potential targets of the major compounds from Rosmarinus officinalis , including the diterpenes carnosic acid, carnosol, and rosmanol, as well as the polyphenolic ester rosmarinic acid.…”
Section: Discussionmentioning
confidence: 99%
“…A study on inhibition of Fts-Z with compounds Coupene, Proximadiol, and Menthone had a docking score of −6.2 Kcalmol −1 , −6 Kcalmol −1 and −5.7 Kcalmol −1 , which are lower than docking score of ADMA dealt in our finding [ 8 ]. Another study on verticiol as a Fts- Z inhibitor exhibits the docking score of −4.72 Kcalmol −1 [ 58 ]. These compounds had binding affinity near to ADMA reported in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Another group of scientists exploring the 180 endophytic fungal strains from Chinese medicinal plant Panax notoginseng found compound Brasiliamide J-a and Brasiliamide J-b from species Penicillium janthinellum to be a potential inhibitor of Fts-Z against B. subtilis (PDB ID-2VXY), with a binding affinity of −111 Kcalmol −1 forming H − bonds with residues Glu 139 and Gly 107 and hydrophobic bonds Asn 166, Gly 104, Gly 21, and Asn 25 for compound Brasiliamide J-a and −122 Kcalmol −1 forming H − bonds with Asn 25 and hydrophobic bonds with Met 105, Glu 139, and Phe 183 for compound Brasiliamide J-b and against S.aureus (PDB ID-3VOB) [ 61 ]. Further, an In-silico study revealed that quinazoline derivatives, Zantrin Z3 and ZZ3, bind Mycobacterium tuberculosis Fts-Z protein (PDB ID- 1RQ7-chain A) near the H6/H7 loop and do not affect hydrolysis of GTP, but they are efficient against the aggregation of Fts-Z [ 58 ]. Ballu and co-workers performed In-silico receptor-based docking experiments and 3D QSAR using CoMFA and CoMSIA methods to understand binding interactions of 42 molecules (oxazole-benzamide derivatives and aryl alkoxy benzamide derivatives) with the receptor (PDB ID- 3VOB) and highlighted the role of residues Val 207, Leu 209, and Asn 263 in the binding of inhibitors to Fts-Z protein [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…E2 and OHT were redocked in the binding sites of ERα1 and ERα2, respectively, to validate the docking procedure and parameters [56]. The complexes from redocking were superimposed with the X-ray crystal structures 1GWR and 3ERT, respectively, to calculate RMSD values for the ligands (Figure 8).…”
Section: Discussionmentioning
confidence: 99%